Analysis of the Influence of Brand Ambassadors and Promotions on Product Purchasing Decisions at Shopee (On Shopee Application Users in Sukoharjo Regency) - Jayusman, Nugroho; Dwi Lestari, Wuryaningsih; Permatasari, Qisthoni (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to analyze whether there is an influence of brand ambassadors and promotions on purchasing decisions for Shopee application users in the Sukoharjo area. The data used for analysis is primary data. Obtaining data by distributing questionnaires was then processed by multiple regression using SPSS. The results of the Hypothesis Test show that Brand Ambassador (X1) has no significant effect on product purchasing decisions at Shopee, after that Promotion (X2) has a significant positive effect on product purchasing decisions at Shopee. Testing these two variables shows different results and it can be concluded that brand ambassadors do not influence product purchasing decisions at Shopee. Conversely, promotions have a positive effect on product purchasing decisions at Shopee for Shopee application users in Sukoharjo Regency.